2003
DOI: 10.1038/sj.gene.6363889
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the SPINK5 gene and atopic dermatitis in the Japanese

Abstract: Atopy, which is characterized by increased levels of immunoglobulin E (IgE) against common environmental allergens, is considered the strongest predisposing factor for asthma and atopic dermatitis (AD). Mutations in the gene encoding serine protease inhibitor Kazal-type 5 (SPINK5) are responsible for Netherton syndrome, a rare skin disorder characterized by greatly elevated IgE levels with atopic manifestations. A recent study of Caucasian AD families showed that maternally derived alleles of the SPINK5 gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 14 publications
2
87
1
3
Order By: Relevance
“…Interestingly, an insertion in the 3′ untranslated region of the kallikrein 7 gene (KLK7) encoding SCCE 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 35 has been reported to be associated with eczema. Early genome wide linkage analysis of eczema family studies suggested a potential locus on 5q31 and, after identification of 6 common polymorphisms in SPINK5, the variant Lys420Ser, was associated with eczema in a cohort of British children, 36 this association has been replicated in 2 small Japanese studies, 37,38 but other studies have failed to replicate this association. {REFS HERE} However, whereas FLG has been firmly established as a major gene for eczema, the reported effects of KLK7 and SPINK5 variants are rather weak and so far lack robust confirmation in replication cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an insertion in the 3′ untranslated region of the kallikrein 7 gene (KLK7) encoding SCCE 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 35 has been reported to be associated with eczema. Early genome wide linkage analysis of eczema family studies suggested a potential locus on 5q31 and, after identification of 6 common polymorphisms in SPINK5, the variant Lys420Ser, was associated with eczema in a cohort of British children, 36 this association has been replicated in 2 small Japanese studies, 37,38 but other studies have failed to replicate this association. {REFS HERE} However, whereas FLG has been firmly established as a major gene for eczema, the reported effects of KLK7 and SPINK5 variants are rather weak and so far lack robust confirmation in replication cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…SPINK5, a serine protease inhibitor involved in the regulation of stratum corneum thickness and function, is another gene of interest in AD. SPINK5 mutations are found in AD associated with Netherton's syndrome [14] and also have been found in some subsets of AD and are felt to confer risk of maternal transmission of AD [15,16]. However, several observations suggest that genetic mutations resulting in barrier impairment are not the only pathogenic factor in AD.…”
Section: Pathogenesis Of Admentioning
confidence: 95%
“…A)) of the SPINK5 gene and AD in a Japanese population and found a positive association of 7 SPINK5 SNPs (except for 1156G > A) with AD. (64,65) In addition a study of Six SNPs rs17718511, rs17860502, KN0001820, rs60978485, rs17718737, and rs1422985 in the SPINK5 gene provides evidence for a significant interaction between the SPINK5 gene that may contribute to AD susceptibility among Korean. (68) …”
Section: -Spink5 and Lekti Genementioning
confidence: 99%
“…(62) Otherwise, a recent study was suggested that the E420K LEKTI variant is a risk factor for AD through an increase in the TSLP expression. (63) Subsequently, recent studies found a significant association between (1258G > A) SPINK5 polymorphism and AD in Japanese, (64,65) and in German. (66) In individuals affected by AD, a significant maternal over-transmission of the risk allele to their children was demonstrated Walley et al (67) Folster-Holset al, studied 8 SNPs in different regions of the SPINK5 gene, including 4 non-synonymous SNPs leading to an amino acid change (Asp106Asn (G316A), Asn368Ser (1103A > G) and Asp386Asn (1156G > A), and, Gly463Gly (A1389G), Val553Val (C1659T), Leu756Leu (C2358T) and Gly804Gly C2412T) and Glu 825Asp (C2475T)).…”
Section: -Spink5 and Lekti Genementioning
confidence: 99%